Physical Profile of West Java Taekwondo Athletes for Pekan Olahraga Nasional XVIII Riau - Pynkan Lafanda; Ambrosius Purba; Tri Damiati Pandji (Althea Medical Journal, 2015)
Background: Taekwondo is a martial sport that is often included in competitions, especially in a national event such as Pekan Olahraga Nasional (PON) XVIII Riau in September 2012. A taekwondo athlete must havemaximum physical condition in order to achieve maximum performance. West Java taekwondo athletes who will participate in this national sport event receive centralized exercises as a special preparation stage. This study aimed to determine the physical condition profile of male and female taekwondo athletes for PON XVIII RiauMethods: A quantitative descriptive study was conducted in September 2012 to 15 West Java taekwondo athletes for PON Riau XVIII consisting of 7 male athletes and 8 female athletes. Physical conditions measured were strength, endurance, power, speed, flexibility, cardiorespiratory fitness, agility, and reaction time. The measurement results were then compared to the physical standards data from the head of National Sports Committee of Indonesia (Komite Olahraga Nasional Indonesia/KONI) and were analyzed by percentagecategoryResults: Characteristics in less category were abdominal muscle endurance (male 71.43% and female 100%), cardio respiratory fitness (male 85.71%), and agility (female 37.50%). Characteristics in far category were cardio respiratory fitness (female 62.50%) and agility (male 57.14%)Conclusion: The ability of the physical condition of male and female West Java taekwondo athletes for Pekan Olahraga Nasional XVIII Riau still needs to be improved to maximize achievement. [AMJ.2015;2(1):281–86]